WATER INTAKE WELLS NEAR WINDOWS SMUHOPODIBNOHO LITHOLOGICAL - and (Municipal economy of cities (Technical science), 2013)
A mathematical model of the flow of underground fluids up tube wells from smuhopodibnoho lithological window. Presented by the decision in the case of single use water intake well in these conditions. The recommendations on accounting for additional filtration resistance smuhopodibnoho lithological window.